PENILAIAN EFISIENSI INVESTASI SAHAM YANG TERINDEKS SAHAM SYARIAH DENGAN METODE CAPITAL ASSET PRICING MODEL (CAPM) (Sektor Industri Barang Konsumsi Pada Indeks Saham Syariah Indonesia Periode Agustus 2018-Juli 2020) - Musthofa Kamal Al Firdausi; Noor Shodiq Askandar; Dwiyani Sudaryanti (e_Jurnal Ilmiah Riset Akuntansi, 2021)
This study aims to describe the efficiency of stock investment by using the CAPM (Capital Asset Pricing Model) as an investment decision-making selection. Investments in the capital market generally have higher returns than investments in the financial markets. Sometimes an investor is confused in choosing which shares to buy, this study describes the CAPM with efficient and inefficient grouping in the consumer goods industry sector. The CAPM method of this research is based on shari’a using the SBIS rate of return, so that Muslim investors continue to invest with Islamic teachings. This research technique uses documentation data collection with secondary data. The sample used in this study was 28 Islamic stocks whose criteria for consistent Islamic stocks were included in the ISSI (Indonesian Sharia Stock Index) for the period August 2018 - July 2020.Keyword : stock; shari’a; efficient; SBIS; SCAPM.